2014
DOI: 10.1212/wnl.0000000000000014
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Reasoning: A 42-year-old man with severe headache, fever, and acute coma

Abstract: A 42-year-old man underwent brain MRI at a local health facility for severe headache and was found to have a pituitary adenoma. Two days later, he presented to the emergency department of our hospital with high fever and sudden-onset coma. The patient had a history of intermittent moderate headache in the recent 8 months. No medical history of vascular risk factors was identified.On examination, his Glasgow Coma Scale score was 4/15, blood pressure was 133/86 mm Hg, and body temperature was 40°C. Blood oxygen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…The UK guidelines suggest that surgery should be performed within the first 7 days of symptom onset in patients with severe and progressive neuroophthalmological deficits [1]. However, some authors caution that early recanalization of the obstructed vessel after decompression, with subsequent reperfusion injury, may be harmful, converting an infarct into a hemorrhage [13,19,20,38]. Consistent with this, our data also suggest that patients who underwent delayed surgeries had better outcomes than those who had emergent surgeries (Table 2).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The UK guidelines suggest that surgery should be performed within the first 7 days of symptom onset in patients with severe and progressive neuroophthalmological deficits [1]. However, some authors caution that early recanalization of the obstructed vessel after decompression, with subsequent reperfusion injury, may be harmful, converting an infarct into a hemorrhage [13,19,20,38]. Consistent with this, our data also suggest that patients who underwent delayed surgeries had better outcomes than those who had emergent surgeries (Table 2).…”
Section: Discussionsupporting
confidence: 83%
“…Cerebral infarction was reported to be caused by both mechanical compression and vasospasm in two patients [37,38]. The overlap between spasm and extrinsic compression did not permit a clear differentiation of these two mechanisms in some situations, as angiography and/or MRA was not always performed.…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, tumour decompression can restore blood flow to the compressed vessels and reduce intratumoural stress, thereby reducing the exudation of blood or vasoactive substances into the subarachnoid space; thus, some neurological deficits can be resolved [2, 30]. However, some authors have reported that surgical decompression might be detrimental to patient recovery if a head CT indicates cerebral infarction and might result in haemorrhagic infarction [10, 30, 47]. In our study, compared to patients who underwent emergency surgery, patients who underwent delayed surgery showed a better prognosis.…”
Section: Discussionmentioning
confidence: 99%